Orientador(a) Escolar. Más Que Un Pedagogo/a. ¿Un cambio de Paradigma? O solamente un cambio en nuestras funciones - Borja, Carlos (Educación y Ciudad, 2019)
"TO ORIENTATE” ¿Does currently have to see with pedagogy, with education, with academics? The verb -to Orientate- that guides us, has changed from being and acting, transforming my occupation: “School Counselor Teacher”, adding Colombian conceptualizations that give it a different and proper meaning, for Latin America and perhaps the world. Our categories, based on reality, contextual in Schools and transcending conceptual and imaginary frontiers about our work, in Public Educational Institutions, reaching the community and impacting Society.